Improvement in Skin Penetration Capacity of Linalool by Using Microemulsion as a Delivery Carrier: Formulation Optimization and In Vitro Evaluation - Ming-Jun Tsai; Wen-Yu Chang; I-Hui Chiu; I-Ling Lin; Pao-Chu Wu (MDPI AG, 2023)
Linalool is an aromatic oil with analgesic, anti-inflammatory and anti-UVB-induced skin damage effects. The aim of this study was to develop a linalool-loaded microemulsion formulation for topical application. In order to quickly obtain an optimal drug-loaded formulation, statistical tools of the response surface methodology and a mixed experimental design with four independent variables of oil (X1), mixed surfactant (X2), cosurfactant (X3) and water (X4) were used to design a series of model formulations in order to analyze the effect of the composition on the characteristics and permeation capacity of linalool-loaded microemulsion formulations and to obtain an appropriate drug-loaded formulation. The results showed that the droplet size, viscosity and penetration capacity of linalool-loaded formulations were significantly affected by formulation component proportions. The skin deposition amount of the drug and flux of such formulations expressively increased about 6.1-fold and 6.5-fold, respectively, when compared to the control group (5% linalool dissolved in ethanol). After 3 months of storage, the physicochemical characteristics and drug level did not show a significant change. The linalool formulation-treated rat skin showed non-significant irritation compared to skin treatments in the distilled-water-treated group. The results showed that specific microemulsion applications might be considered as potential drug delivery carriers for essential oil topical application.